2023
DOI: 10.3390/sym15030613
|View full text |Cite
|
Sign up to set email alerts
|

PSO-Based Ensemble Meta-Learning Approach for Cloud Virtual Machine Resource Usage Prediction

Abstract: To meet the increasing demand for its services, a cloud system should make optimum use of its available resources. Additionally, the high and low oscillations in cloud workload are another significant symmetrical issue that necessitates consideration. A suggested particle swarm optimization (PSO)-based ensemble meta-learning workload forecasting approach uses base models and the PSO-optimized weights of their network inputs. The proposed model employs a blended ensemble learning strategy to merge three recurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Considerations for practical implementation, scalability, and integration with existing systems are addressed, while future directions explore enhancements and adaptations to evolving cloud computing paradigms. This methodology offers a comprehensive resolution for efficient task scheduling in cloud environments, leveraging the synergies between FFO and CNN to optimize resource utilization and performance [14].…”
Section: Proposed Methodology: Maximizing Resource Utilization In Clo...mentioning
confidence: 99%
“…Considerations for practical implementation, scalability, and integration with existing systems are addressed, while future directions explore enhancements and adaptations to evolving cloud computing paradigms. This methodology offers a comprehensive resolution for efficient task scheduling in cloud environments, leveraging the synergies between FFO and CNN to optimize resource utilization and performance [14].…”
Section: Proposed Methodology: Maximizing Resource Utilization In Clo...mentioning
confidence: 99%
“…This challenges the ensemble models to consider such techniques, which results in the best accuracy and productivity metrics. 7,8 Therefore, this paper has devised an ensemble technique for host load prediction using diverse time-series forecasting models.…”
Section: Motivation and Our Contributionsmentioning
confidence: 99%
“…H. L. Leka et al 8 suggested a particle swarm optimization (PSO)‐based ensemble meta‐learning workload forecasting approach. The proposed model employs a blended ensemble learning strategy to merge three recurrent neural networks (RNNs), followed by a dense neural network layer.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the cloud environment is dynamic, task arrivals, departures, and resource requirements are always changing. This dynamic nature renders the requirement for task scheduling algorithms that can be flexible and adaptive in real time to quickly adjust to changing demands [7]. Finally, to accomplish load balancing and maximize resource utilization, efficient task scheduling that relies on the appropriate distribution and application of resources is needed.…”
Section: Introductionmentioning
confidence: 99%